Advances in Artificial Intelligence - Bergler, Sabine (Springer, 2017)
This book constitutes the refereed proceedings of the 21st Conference of the Canadian Society for Computational Studies of Intelligence, Canadian AI 2008, held in Windsor, Canada, in May 2008.